Performance of Rapid Antibody Test and RT-PCR as Frontline Test for COVID-19 Diagnosis in Pregnancy: an Experience in Indonesia - Evert S. Pangkahila; Ryan S. Mulyana; Hariyasa Sanjaya; Mulyantari K; Daniel H. Susanto (Journal Research of Social Science, Economics, and Management, 2022)
Ensuring an accurate diagnosis is critical for limiting the spread of SARS-CoV-2 and for the clinical management of COVID-19, especially in pregnant women. For now real-time reverse transcription polymerase chain reaction (RT-qPCR) is the currently recommended laboratory method for the diagnosis of acute SARS-CoV-2 infection. More recently, several easy-to-perform rapid antigen detection tests have been developed and are recommended as first-line screening test in several countries. The purpose of this study was to evaluate the comparative performance of a rapid antibody test and RT-PCR for the detection of SARS-CoV-2 infection, as a front-line test for the diagnosis of COVID-19 in pregnancy. This research method is a descriptive study to describe comparation of sensitivity and specificity between rapid SARS-CoV-2 antibody test to the gold standard nasopharyngeal RT-PCR swab test. Of the 271 samples, only 257 were eligible and fourteen cases were excluded from the study due to a lack of rapid antibody test and RT-PCR results. The results of this study showed that the rapid SARS-CoV-2 antibody test sensitivity was 80.95%, and the specificity was 90.68%, the NPV (negative predictive value) and the PPV (positive prognosis value) were 98.17% and 43.59%, respectively. Based only on the results of IgM and IgG, IgM and IgG sensitivity were 33.33% (7/21) and 71.43% (15/21), respectively, and the specificity was 91.1% (215/236, 21 false positive) and 91.53% (216/236, 20 false positive), respectively. The use of rapid antibody tests during pregnancy is a screening tool and is not currently applicable for diagnostic tool. To minimize false positives and negatives results, the use of rapid antibody tests should be combined with the RT-PCR test results.